Design of a Web-Based Viar Electric Motor Unit Ordering System Using the Waterfall Method - Saragih, Putri Chrystin; Wijaya, Edi; Tarigan, Feriani Astuti (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
The development of electric vehicles, particularly electric motorcycles, is gaining increasing public interest due to their environmental friendliness and lower operational costs. One emerging electric motorcycle brand is Viar. However, the current system for ordering Viar electric motorcycles is still done manually, such as by telephone or directly with dealers, which is inefficient and potentially prone to errors in recording. To address this issue, this study designed a web-based Viar electric motorcycle ordering system with the goal of making it easier for customers to order online, improving data accuracy, and speeding up the transaction process. The system was developed using the Waterfall method, which consists of the following stages: (1) needs analysis, (2) system design, (3) coding, (4) testing, and (5) implementation. The result of this study is a web application that allows customers to view the Viar motorcycle catalog, select a unit, place an order, and receive real-time order confirmation. Dealers can also manage stock and transactions in a more structured manner. This system is expected to improve Viar’s business efficiency and make it easier for consumers to purchase electric motorcycles. Keywords: Viar Electric Motorcycles, Online Ordering, Web, Waterfall Method.